Dinamika Sains dalam Islam pada Masa Keemasan: Kontribusi & Rekonstruksi dalam Perkembangan Keilmuan Kekinian - Tri Wibowo (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2021)
This article discusses the track record of the development of Islamic science in the golden age (Abbasid Dynasty) which has a very significant contribution to the development of contemporary science. The reason for taking the topic is to know and study more deeply about the contributions and triggers of the rapid progress of Islamic science during the Abbasid Dynasty so that it can be reconstructed for the development and progress of contemporary science. The contribution of Islamic science in the golden age (Abbasid Dynasty) to the Western Renaissance was to provide an ideal model of human civilization imbued with Islamic values that could support the realization of civil society that had a collective awareness of the rights and obligations that must be carried out. The existence of collective awareness can encourage the achievement of the ideals of a community effectively and efficiently. Reconstruction took the form of reviving movements in the field of science such as strengthening the philosophical foundation of Islamic science that is unique in the realm of epistemology. The epistemological domain includes sources of knowledge, methods and instruments of knowledge. The sources of knowledge in Islam are al-Qur'an and al-Hadith which are understood through the universe, reasons and history. The method of obtaining knowledge uses dialectical methods as well as instruments used to acquire knowledge in Islam through the senses, ratios and intuition.